Cracks in the Ice. - Cracks in the Ice ([Australia] : Cracks in the Ice)
"Cracks in the Ice is an online toolkit providing trusted, evidence-based, and up-to-date information and resources about crystal methamphetamine (ice) for the Australian community. In April 2015, the Commonwealth Government established a National Ice Taskforce to provide advice to Government on the impacts of ice (crystal methamphetamine) in Australia and actions needed to address this growing problem. The Final Report of this Taskforce stated that "The first priority must be supporting families, workers and communities to better respond to people affected by ice." (Commonwealth of Australia, Department of the Prime Minister and Cabinet, Final Report of the National Ice Taskforce, 2015). As part of a co-ordinated response to this need the Australian Government Department of Health funded development of Cracks in the Ice, an online toolkit to provide evidence-based information about ice (crystal methamphetamine) for the Australian community."--About Cracks in the Ice.
Title from title screen (viewed on 22 August 2017)
Mode of access: Available Online. Address as at 28/08/2017
Selected for archiving
Keywords: Drug abuse -- Australia; Australian